Genetypes: a concept to help integrate molecular phylogenetics and taxonomy - Chakrabarty, Prosanta (Zootaxa, 2010)
In order to better integrate molecular phylogenetics and taxonomy, genetic sequences from type materials should be explicitly identified in publications using a consistent nomenclature. Despite relatively frequent sampling of sequences from types (particularly topotypes—samples from the type locality), the practice of explicitly noting that these materials were sampled is uncommon. Because of the lack of an explicit nomenclature tied to taxonomy, the existence of genetic “type sequences” is obscured. Also hindering progress in taxonomy is the increasingly uncommon practice of reporting locality and voucher information (e.g., GPS coordinates, museum catalog numbers) on repositories such as GenBank. To remedy this problem and bring awareness to the situation, I propose the use of the term “genetype” as a label for any sequence data from types (including from holotypes, secondary types, topotypes, etc.).